UTILIZING GRAPHIC DESIGN MEDIA IN THE DEVELOPMENT OF ARABIC LANGUAGE LEARNING - Azizah, Nuril (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Graphic design is a vital skill across various fields, including Arabic language learning. This skill can be leveraged to produce artistic, informative educational media, thereby enhancing the motivation of both teachers and students in the learning process. This study employs a qualitative descriptive methodology utilizing a literature review approach. Data were collected through the examination of books, journals, and other relevant sources, carefully analyzed in relation to the topic, and then articulated in the researcher's own words, relevant to the context of contemporary Arabic language education. The findings of this study indicate that students are more enthusiastic about participating in the learning process, find it easier to assimilate material, and that graphic-based media can aid teachers in their instructional efforts.